(untitled) (Zaporizhzhia Historical Review, 2021)
In the article represents all the known fund of written testimonies about the tivertzi and the ulitchi, the tribes who lived in the Carpathian – Black Sea – Region. This generalized vision of the point discovers some new perspctives for further studies of the origin, development and historical destiny of the mentioned tribes.